How do acquisitions affect the mental health of employees? - Laurent Bach; Ramin P. Baghai; Marieke Bos; Rui Silva (Tinbergen Institute, 2021)
Using employer-employee level data linked to individual health records, we document that the incidence of stress, anxiety, depression, psychiatric medication usage, and even suicide increase following acquisitions. These effects are prevalent among employees from both targets and acquirers, in weak as well as in growing, profitable firms. Employees who experience negative career developments within the merging firms, 'blue-collar' workers, and employees with lower cognitive and non-cognitive skills are most affected. A variety of tests address endogeneity concerns, including an analysis exploiting failed mergers. Our findings point to mental illness as a significant non-pecuniary cost of acquisitions.
Keywords: G34; I10; J81; L23; 330; Mergers and Acquisitions; Corporate Restructuring; Mental Health; Mental Illness